'Nearly gave up on it to be honest': Utilisation of individualised budgets by people with psychosocial disability within Australia's National Disability Insurance Scheme. (30th June 2022) - Devine, Alexandra; Dickinson, Helen; Rangi, Mediya; Huska, Marie; Disney, George; Yang, Yi; Barney, Jody; Kavanagh, Anne; Bonyhady, Bruce; Deane, Kirsten; McAllister, Ashley
Abstract: Utilisation of budgets provides important insights into the effectiveness of individualised funding schemes. Significant under‐utilisation by certain cohorts may indicate schemes are not working as intended. People with psychosocial disability have been identified as one such cohort experiencing barriers to effective budget utilisation within Australia's National Disability Insurance Scheme. Our mixed‐methods research confirms that while this cohort receive sufficient budgets, their spending is lower in comparison to other participants. Addressing under‐utilisation drivers arising from complex interactions between individual, systems, and contextual‐level factors, requires intervention within individualised funding schemes and the broader policy environment.